A naturalização da permanência da violência policial no Estado democrático de direito brasileiro revelada a partir do "habitus" autoritário - Kussi, Nicoly (2020)
The aim of this dissertation was to think about the reason for the naturalization of the permanence of police violence in the democratic State governed by the rule of law with Pierre Bourdieu's habitus theory mobilization. Based in the existence of an authoritarian habitus structured by the social order, by how institutions are operated and by the State and police being structured in an authoritarian manner, the violation of the rights of part of the population occur and are contrary to the constitutional precepts. The results indicate that the law and the justice system have acted in order to legitimize and to approve the police action that violates the Constitution, and that contributes to the permanence of this violence in the democratic rule of law. In this sense, with the dialectic between structures, which act in an authoritarian way, and authoritarian habitus in a resonant way, the permanence of police violence in the democratic rule of law becomes naturalized.